PRAGMATIC SEMANTIC FEATURES OF THE TEXT IN KOREAN AND UZBEK LANGUAGES - Melikova U. (Journals Park Publishing, 2022)
The article provides a comparative analysis of pragmatic-semantic expressions in Uzbek and Korean. Many masterpieces of Uzbek literature are used to illustrate the topic of the article.
Keywords: pragmatic; semantic; Uzbek